KEKERASAN SIMBOLIK DAN REPRESENTASI GENDER DALAM MEDIA: ANALISIS LINGUISTIK KRITIS PEMBERITAAN KASUS MUTILASI PACET MOJOKERTO - Niken Aldila Safina Putri; Cita Wieke Mebrila; Muhammad Dhaniel Affandi; Ingghar Ghupti Nadia Kusmiaji (JIP: Jurnal Ilmu Pendidikan, 2026)
This study examines symbolic violence and gender representation in the reporting of the Pacet Mojokerto mutilation case using Norman Fairclough's Critical Discourse Analysis (CDA). This study employed a qualitative approach, with data sources consisting of news videos on the YouTube platform and their narrative transcripts. The analysis focused on discourse practices, including the production, distribution, and consumption of texts. The results showed that the media reproduced gender bias through the use of sensationalist diction, causal framing that led to victim blaming, and the dominance of law enforcement narratives. The distribution of discourse through digital media reinforced the spread of patriarchal ideology, while audience consumption of texts contributed to the normalization of violence against women. This study emphasized that media discourse practices play a significant role in shaping public perception and reproducing gender inequality in crime reporting